An innovative fixture for testing the crashworthiness of composite materials - Lorenzo Vigna; Iman Babaei; Ravin Garg; Giovanni Belingardi; Davide Salvatore Paolino; Andrea Calzolari; Giuseppe Galizia (Fracture and Structural Integrity)
Despite the growing diffusion of composite materials in automotive and aerospace sectors, a standard procedure for testing their crashworthiness has not been developed yet. At present, the international standards for testing composite materials under impact conditions are not adequate to test their crush behavior.